Adoption of Recommended Management Practices by the Buffalo Owners - Aulakh, G S; Singh, Rajbir (Indian Journal of Dairy Science, 2012)
The present study was conducted in three districts of Punjab on 180 buffalo owners to measure the extent of adoption of recommended management practices. The study revealed that buffalo owners had medium level of adoption of recommended management practices. High adoption was found in case of adequate supply of feed and water to the buffalo (95%), followed by udder cleaning (90.56%) and keeping of buffalo in ventilated houses (82.22%). The low adoption rates were observed in the practices of separation of pregnant buffalo few days before calving (18.89%) and wallowing of buffalo in the pound (23.33%). The education level of the respondent was positively and significantly co-related with the adoption of recommended management practices.